Safety and early efficacy of endoscopic sleeve gastroplasty (ESG) for obesity in a multi‐ethnic Asian population in Singapore. Issue 12 (3rd December 2021) - Asokkumar, Ravishankar; Lim, Chin Hong; Tan, Ai Shan; Lee, Phong Ching; Eng, Alvin; Tan, Jeremy; Lopez‐Nava, Gontrand; Ganguly, Sonali; Chang, Jason; Khor, Christopher
Abstract: Background and Aim: Endoscopic sleeve gastroplasty (ESG) is an alternative nonsurgical treatment option for obesity. However, most studies on the utility and efficacy of ESG are derived from the Western population. It is unknown if ESG elicits similar results in Asians with different fat distribution, sociocultural customs, and dietary practices. Our study aims to assess the safety and efficacy of ESG among a multi‐ethnic Asian population. Methods: We reviewed 35 patient records who underwent primary ESG for obesity at our unit. We followed a U‐shaped suture pattern. Our primary outcome was to assess technical feasibility and safety. The secondary outcome was to determine the percentage total body weight loss (TBWL) at the last follow‐up. Results: The mean ± SD age and body mass index were 43.6 ± 11.3 years and 34 ± 4.9 kg/m 2, respectively. The majority were female (57%) and of Chinese ethnicity (51%). The procedure was technically successful in all patients. We used an average of five sutures (range, 4–7), and the mean ± SD procedure time was 65 ± 10 min. No major complications occurred, and the average length of stay was 1 day. Twenty‐one patients completed 3 months of follow‐up, and 10 patients 6 months. The mean ± SD TBWL at 3 and 6 months were 14.5 ± 4.8% and 16.2 ± 4.9%, respectively. We observed improvement in diabetes mellitus (87%), fatty liver (86%), and hypertension (58%) during the follow‐up. Conclusion: ESG is a safe and effective option for promoting weight loss in a multi‐ethnic Asian population. ESG‐induced weight loss may improve obesity‐related comorbidities. Abstract : Endoscopic sleeve gastroplasty (ESG) is an effective treatment option for Asian patients with obesity. ESG is a short‐stay procedure with an excellent safety profile, and the weight loss achieved leads to improvement in comorbidities.